Doing Philosophy of Technology - Pitt, Joseph C. author. aut Link
XVIII, 222 p.
Keywords: As science becomes more deeply embedded in a complex technological infrastructure, has this changed the relationship between the sciences and the various technologies that support them? As our technologies help shrink our world, can we restrict our ethical concerns or must we find a way to face the fact that we are now one world? What do new forms of architecture say about whom we are? Is the design process the new epistemological paradigm? The answers to all of these is "yes" according to Joseph C. Pitt (VirginaTech). Doing Philosophy of Technology presents an updated and integrated overview of the most important thinking from this prominent philosopher of technology. Throughout his career Joseph C. Pitt has defended the view that to say anything meaningful about the value of a technology one must know something about that technology and how it functions in the world. This starting point leads naturally to a pragmatist philosophical stance, since it is the real world consequences of introducing a technology that must be the basis for any further normative judgements. In the book we find an extended set of arguments that challenge the idea that there are eternal philosophical issues that transcend the impacts that technologies make on human beings and their world. Rather, it is claimed that as our technologies transform our world they transform us and the kinds of questions we find important to answer.